Sosialisasi dan pengawasan oleh pemerintah sebagai upaya pemberantasan praktik pungli - Jannah, Khurfatul; Nabila, Zahwa Aziza; Musyafa’, Muhammad Hammam; Fawaid, Muhammad (Maliki Interdisciplinary Journal, 2025)
The practice of illegal levies (pungli) in Indonesia has become a serious problem that undermines public trust in government institutions and creates injustice in public services. This research aims to develop solutions for the eradication of illegal levies in Indonesia, focusing on the analysis of socialisation, monitoring and the role of the government. Using a qualitative method with an analytical descriptive approach, this research collected secondary data from literature studies, including laws and regulations related to extortion practices. The results of the analysis show that although the government has undertaken various socialisation efforts and established the Sapu Bersih Pungutan Liar Task Force (Satgas Saber Pungli), significant challenges remain, such as low public awareness of the law and ineffective supervision. The study recommends several practical solutions, including increased public education campaigns on the dangers of extortion, stronger on-the-ground monitoring mechanisms, and closer cooperation between the government, the community and the private sector. It is hoped that these concrete steps will significantly reduce extortion practices, increase public trust in government institutions and create a more transparent and accountable environment.